Między monetaryzmem a gospodarką regulowaną : wpływ światowego kryzysu na rynkach finansowych (2008–2009) na modernizację liberalnych teorii rozwoju gospodarczego - Koćwin, Julitta (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Crisis in the financial markets (2008–2009), often referred to as the “financial bubble,” questioned the monetarist theory shaped in the second half of the 20th century, whose precursor was Milton Friedman. Decrease in the rate of economic growth in highly developed Western economies, which was a result of that crisis, forced leading economists to critical opinions on the commonly adopted monetarist (neoliberal) system of market economy. American economist Paul Krugman (U.S. President Barack Obama’s economic advisor) became a proponent of returning to controlled market economy and supported state intervention in the economy. The article is a contribution to the discussion about the new model of market economy which would exclude market failures
Keywords: kryzys finansowy; monetaryzm; interwencjonizm; rynek kontrolowany